KENAKALAN DAN PENYALAHGUNAAN NARKOBA PADA REMAJA BESERTA UPAYA PENCEGAHANNYA - Khoriani, Elwiza; Shofiah, Vivik (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Teenagers are an asset for the future of a nation. However, nowadays there is a lot that happens to teenagers, such as drugs. This is a familiar problem. Juvenile delinquency includes all behavior that deviates from criminal law norms committed by teenagers. There are many internal and external factors that cause juvenile delinquency that need to be considered. Juvenile delinquency is a social disorder that is a global problem, including in Indonesia. Abuse of narcotics, psychotropic substances and addictive substances (NAPZA) among teenagers is one form of delinquency committed by teenagers. To overcome this, guidance from parents and a good environment is very necessary. The research method in this paper is based on library research. The results of the research explain that to overcome juvenile delinquency, especially narcotics abuse, guidance from parents and a good environment is very necessary.